Clcn4-2 genomic structure differs between the X locus in Mus spretus and the autosomal locus in Mus musculus: AT motif enrichment on the X - Nguyen, Di Kim; Yang, Fan; Kaul, Rajinder; Alkan, Can; Antonellis, Anthony; Friery, Karen F.; Zhu, Baoli; de Jong, Pieter J.; Disteche, Christine M. (Genome Research, 2011)
In Mus spretus, the chloride channel 4 gene Clcn4-2 is X-linked and dosage compensated by X up-regulation and X inactivation, while in the closely related mouse species Mus musculus, Clcn4-2 has been translocated to chromosome 7. We sequenced Clcn4-2 in M. spretus and identified the breakpoints of the evolutionary translocation in the Mus lineage. Genetic and epigenetic differences were observed between the 5′ends of the autosomal and X-linked loci. Remarkably, Clcn4-2 introns have been truncated on chromosome 7 in M. musculus as compared with the X-linked loci from seven other eutherian mammals. Intron sequences specifically preserved in the X-linked loci were significantly enriched in AT-rich oligomers. Genome-wide analyses showed an overall enrichment in AT motifs unique to the eutherian X (except for genes that escape X inactivation), suggesting a role for these motifs in regulation of the X chromosome.